2020
DOI: 10.1111/iwj.13317
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prevalence of pressure ulcers in cancer patients admitted to hospice: A multicentre prospective cohort study

Abstract: Pressure ulcers lead to discomfort for patients and may have an important impact on a patient's quality of life. Measure the incidence and prevalence of pressure ulcers in a Hospice environment; evaluate the risk factors associated with pressure ulcers; and calculate the incidence of Kennedy Terminal Pressure Ulcers. This multicentre prospective cohort study enrolled 440 cancer patients in advanced phase, consecutively admitted to five hospices of the AUSL della Romagna (Italy), during a period of 1 year. Five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…We thought that such high rates of tracheostomy and PEG could be explained by the longer-term survival of primary brain tumor patients compared to patients with metastatic brain tumors. The study by Jakobsen et al [21] demonstrated that advanced age, proximity to death, long hospital stays, and a poor clinical condition increased the risk of PU development.…”
Section: Discussionmentioning
confidence: 99%
“…We thought that such high rates of tracheostomy and PEG could be explained by the longer-term survival of primary brain tumor patients compared to patients with metastatic brain tumors. The study by Jakobsen et al [21] demonstrated that advanced age, proximity to death, long hospital stays, and a poor clinical condition increased the risk of PU development.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of a TU classification system and assessment tool has unintended consequences for clinicians and researchers because it compels them to use tools designed for the assessment, classification, and subsequent reporting of PI 14,16,21 . For example, care and management strategies for PI in individuals at EOL are described in the international PI clinical practice guidelines; however, care and management strategies for unavoidable injuries such as KTU and TB-TTI are not 22 .…”
Section: Introductionmentioning
confidence: 99%
“…The factors that influence peri‐operative PI formation are complex, which mainly include predisposing factors that affect personal health, 10 such as age, 11 , 12 gender, 13 comorbidities (eg, diabetes, cancer, or nervous system diseases), 14 , 15 , 16 malnutrition or obesity, 14 , 17 anaemia, 18 , 19 and smoking, 20 as well as facilitating factors, which refer to factors that exacerbate PIs during surgery, 10 such as the method of anaesthesia, 21 the duration of anaesthesia, 22 , 23 the amount of blood loss, 24 , 25 and patient positioning. 21 , 26 …”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, preventing PI formation, especially severe PIs, is extremely crucial. 3,9 The factors that influence peri-operative PI formation are complex, which mainly include predisposing factors that affect personal health, 10 such as age, 11,12 gender, 13 comorbidities (eg, diabetes, cancer, or nervous system diseases), [14][15][16] malnutrition or obesity, 14,17 anaemia, 18,19 and smoking, 20 as well as facilitating factors, which refer to factors that exacerbate PIs during surgery, 10 such as the method of anaesthesia, 21 the duration of anaesthesia, 22,23 the amount of blood loss, 24,25 and patient positioning. 21,26 The above discussion demonstrates that both facilitating factors during surgery and personal predisposing factors influence the severity of PIs in patients.…”
Section: Introductionmentioning
confidence: 99%